The effect of different doses levels of silver nanoparticles (AgNPs) on the kidney and liver in Albino male Rat. Histopathological study (Baghdad Science Journal, 2014)
Objective: In this study ,the effects of silver nanoparticles (Ag NPs)were investigated on the liver and kidney tissues. Methodology: The produced nanoparticles have an average particle size of about 30 nm. Eighteen male albino rats were used by dividing them into three groups, each group comprise 6 rats. First group(control group) given food and water like other groups by liberty. Second group was tail injected by (AgNPs) at dose of (0.4 mg/kg. body weight/day). Third group was injected by (AgNPs) at dose of (0.6 mg/kg. body weight/day) for 15 days. All animals were sacrified at the end of experiment. The liver and kidney tissues specimens were fixed in 10% formalin and histological preparations were carried out then stained with H&E. Pathological changes in liver and kidney tissues were showed. Results: Histopathological studies revealed the harmful effect of the silver nanoparticles uses on the liver and kidney rats, second group that treated with Ag NPs (0.4 mg/kg.body.weight/day), kidney sections showed enlargement of collecting tubules, increase in interstitial tissue medulla, necrosis and enlargement in proximal and distal convoluted tubules. Liver showed enlargement of the central vein and degeneration of hepatic cells. Third group that treated with Ag NPs (0.6 mg/kg. body weight/day); kidney sections showed hyperplasia of the interstitial connective tissue of renal medulla with hemorrhages, renal cortex showed, degenerative changes and necrosis of proximal and distal convoluted tubules. Liver section showed congestion and necrosis of hepatic cells. Conclusion: Silver nanoparticles cause damage in liver and kidney tissues. Recommendation: Further study is needed for the effect of Ag NPs on the other tissues.